Bangladesh Development Update, April 2016 : Moving Forward with Fading Tailwinds - World Bank (Dhaka, Bangladesh, 2016)
The objective of this report is to update the Government of Bangladesh, think tanks and researchers, the general public as well as the Bank’s senior management on the state of the economy, outlook, risks, progress on structural policy reforms, and key challenges the economy is currently facing. The coverage includes developments in the real sector focusing on growth, inflation, and poverty; external sector developments focusing on the balance of payments, foreign exchange reserves, and the exchange rate; fiscal developments focusing on revenue mobilization, public expenditures, and deficit financing; financial sector developments focusing on credit and interest rates; and monetary developments focusing on reserve money and broad money growth trends. The update also covers an assessment of Bangladesh’s prospect of graduating out of the least developed country (LDC) status and eligibility for concessional financing from the World Bank and the Asian Development Bank.